PENAMBANGAN DATA FORMAT TEXT EXCEL DENGAN SOFTWARE TANAGRA - Julsam Julsam; Handryawan Adnan Mooduto (Teknik Elektro Politeknik Negeri Padang, 2009)
This article describes about Tanagra software application on data mining. Tanagra is data mining software which can be used to access some existing data mining method. Data is built using excel with text data type. This application use the dataset of women with begnin or malignant. The result inform from 699 sample for Univariate Continuous Statistic have begin 65,52% and malignant 34,48%. The other information is the begnin has less mitos (1,6 : 1,59), the malignant has more ucellshape (6,56 : 3,21)